Interpretability of English medical discourse into Lubukusu - Masika, Mary Nasambu; Barasa, David; Mudogo, Benard (Research Journal in Advanced Humanities, 2023)
In this era of massive travel and inevitable migration, many doctors encounter patients with whom they do not share a common language. Whenever doctors encounter patients with whom they have no common language, interpretation is the most solicited solution. This paper examines the interpretability of English - Lubukusu medical discourse in Bungoma County in Kenya. English has unique scientific jargon used in the medical field which have no equivalents in Lubukusu. This study sought to establish the degree to which such terminologies are interpretable from English into Lubukusu in medical consultations. The consultants for the study were two non-native doctors at each of the six selected hospitals in Bungoma County in Kenya, their interpreters and six Standardized Patients (nurses) working at the health facilities and six real patients. The researcher audio recorded two consultation sessions for every doctor with one patient or SP on different appointments and analyzed the data majorly by qualitative methods. The results of this study reveal that there are English medical terms that have no equivalents in Lubukusu hence are non-interpretable. The results suggest ways that can be utilized by governments in ensuring that their citizens benefit most from the presence of the doctors from other countries in their hospitals.